Psychopathy in adult male offenders from Latin America: an item response theory analysis of the self-report psychopathy-short form (SRP-SF) - Trajtenberg, Nicolás; de Ribera, Olga Sánchez; León-Mayer, Elizabeth; Menese, Pablo; Neumann, Craig S. (Frontiers in Psychology, 2026)
IntroductionResearch on the item properties of the Psychopathy Checklist–Revised (PCL-R) is extensive, and the Self-Report Psychopathy Scale-Short Form (SRP-SF) is a derivative of the PCL-R. To date, studies on the SRP-SF items have primarily relied on classical test theory with Western populations, although research using latent variable models across different cultures is emerging.MethodsThis study applied an Item Response Theory approach using the Graded Response Model to examine SRPSF item properties in two incarcerated male samples from Chile (N = 208) and Uruguay (N = 331). It also examined the item functioning differences between these two samples.ResultsFindings indicated that Facet 1 (Interpersonal) was the most informative for measuring the latent psychopathy trait. However, six items showed low discrimination and evidence of differential item functioning (DIF). Only two items displayed DIF between individuals with low versus high psychopathy, while seven items showed DIF across country comparisons.ConclusionModifications are recommended, consistent with previous Latin American research, to further enhance the validity of the SRP-SF in forensic populations in this region.